Sunscreen Innovation Using Aceh Patchouli Oil Extraction - Elly Sufriadi; Suraiya Kamaruzzaman; Putri Athaya Maulida; Ismi Zatya; Intan Mulia Savira; Zulfahmi Zulfahmi; Friesca Erwan (Journal of Patchouli and Essential Oil Products, 2022)
Sunscreen aims to protect the skin from direct sun exposure. This cosmetic product is included in the type of cream. Sunscreen is made from patchouli oil as the main ingredient. The ingredients used in making the sunscreen in each package contain Niacinamide, Avobenzone, Patchouli Oil, Emulgade SE-PE, Cutina GMS SE, Isopropyl Myristate, Dimethicone, Cetiol CC, Glycerin, Phenoxyethanol, Disodium EDTA, and Aquades (ionize water). The tools used are hot plates, scales, magnetic stirrer, stirring spoons, measuring cups, baking glasses, and pipettes. This sunscreen production method is divided into two phases, namely phase A and phase B. In phase A Niacinamide and Avobenzone are mixed at a speed of 2500 rpm, Temperature 70o C for 15 minutes. In phase B, Phenoxyethanol, Disodium EDTA, and Aquades were mixed at a speed of 2500 rpm, a temperature of 70o C for 15 minutes. The next step is that the two phases are mixed at a speed of 1000 rpm, a temperature of 40o C for 10 minutes until homogeneous, then packaged. The results of the research will be carried out by laboratory tests. The indicators to be tested are organoleptic test, homogeneity test, pH test, cream irritation test and photoprotector activity test. The results of each organoleptic test of sunscreen were white, soft texture, patchouli oil aroma, stickiness on the skin was classified as sticky. Homogeneity test showed homogeneous sunscreen, the test was carried out using glass preparations. A certain amount of cream is applied to the slide and visually observed. This test was repeated three times. The cream pH test was carried out using a pH meter, carried out with a number of creams dissolved in aquades and dipped in a pH measuring instrument. Based on the irritation test, sunscreen does not cause irritation. The test was carried out in vivo, the cream was applied to the back of the hand repeatedly for 3 days to 10 respondents aged 19-22 years.